HYDRO ACCESS: SMART WATER DISPENSER WITH QR AUTHENTICATION - Namratha S; K. Avinash; Naveen D; Nitesh Gornale; Prasad Patil (International Educational Journal of Science and Engineering, 2026)
Conventional water dispensing infrastructure deployed in institutions, corporate workplaces and public spaces suffers from critical operational deficiencies including unhygienic contact based interactions, unregulated consumption significant water wastage and the complete absence of centralized resource monitoring. This paper presents Hydro Access a low cost, contactless and IoT capable smart water dispensing framework that integrates QR code based user authentication with embedded hardware automation to overcome these persistent challenges. Each registered user is assigned a unique QR credential that functions as a digital access key. Upon presenting the credential to the ESP32 CAM vision module, the system decodes and validates the identity locally before engaging the dispensing mechanism. An Arduino microcontroller serves as the primary control unit, orchestrating the relay driven water pump, managing an IR based container detection interlock to prevent spillage and providing real time operational feedback through an LCD interface. The system enforces strict access control by rejecting unregistered credentials entirely, thereby limiting water access exclusively to authorized individuals. Prototype validation trials demonstrated a QR authentication success rate of 94.6%, container detection accuracy of 96.2%, volumetric dispensing precision within ±4.8% and a mean authentication latency of approximately 1.8 seconds. The architecture also supports optional integration with cloud platforms such as Firebase for real time consumption tracking quota enforcement and centralized management dashboards. Hydro Access represents a scalable, sustainable and future ready approach to smart water resource management suitable for campuses, hospitals government facilities and public infrastructure.